Burnout among Iranian nurses: a national survey - Sara Mahmoudi; Maasoumeh Barkhordari-Sharifabad; Amir-Hosein Pishgooie; Foroozan Atashzadeh-Shoorideh; Zahra Lotfi (BMC, 2020)
Abstract Background Nurses, particularly critical care nurses, are exposed to high levels of stress and burnout. Burnout is associated with many deleterious consequences affecting health care outcomes. The present study is intended to determine the dimensions of burnout in nurses on surgical, medical and critical care units and its relationship with demographic characteristics. Methods In this descriptive research study, performed at critical and non- critical care units, 743 nurses were randomly selected by quota sampling from medical sciences universities in Iran. Data collection instruments included a "demographic questionnaire" and the "Persian version of the Copenhagen Burnout Inventory. Data were analyzed using SPSS20. Results The findings showed that regarding all dimensions, the lowest level of burnout belonged to surgical wards whereas the highest level pertained to critical care wards indicating a significant difference among various aspects of burnout in different wards, i.e., surgery, medical, and critical care. There was no significant difference in gender, academic degree, and marital status in any of the aspects of burnout in critical care units; yet, the difference was significant between surgical and medical wards (P < 0.05). There were a negative significant correlation between some dimensions of burnout with age and nursing experience in critical care and medical wards (P < 0.05). Whereas in surgical wards, there were a positive significant correlation between some aspects of burnout with nursing experience and age (P < 0.05). Conclusion This study found that the critical care nurses have significantly higher level of burnout compared to the medical-surgical nurses. These results should be considered when planning burnout prevention schedules for nurses.